Pengaruh CAR, FDR dan NPF terhadap ROA Perbankan Syariah dengan PBH sebagai Variabel Moderating - solika, siti lina; Annisa, Arna Asna (Jurnal Keuangan dan Perbankan Syariah, 2023)
This study aims to determine the effect of the Capital Adequacy Ratio (CAR), Financing to Debt Ratio (FDR) dan Non Performing Financial (NPF) to Profitabilityat Islamic Commercial Banks with Profit Sharing Financing as the Moderating variable. This research uses quantitative research using multiple linear regression analisys. The data in this study are secondary data, with the population of Islamic Commercial Banks in 2016-2020. The sampling technique used purposive sampling and obtained a sample of 10 Islamic Commercial Bank that met the criteria. The analysis tool uses the Eviews 9 application. Based on the f test, it is known that simultaneously the variable CAR, FDR, NPF and Profit Sharing Financing have an effect on Profitability. From the R2 test, it is known that the independent variable in this study affects the dependent variable by 99,6%. Based on the t-test, the result show that CAR has a significant positive effect on Profitability, FDR has no effect on Profitability, NPF has no significant positive effect on Profitability, Profit Sharing Financing has no effect on Profitability. From the result of the MRA test, it is known that PBH strengthens the effect of CAR on Profit Sharing Financing, PB weakens the influence of FDR on Profitability, while PBH is unable to moderate the effect of NPF Profit Sharing Financing.